How Aging Affects Sleep-Dependent Memory Consolidation? - Harand, Caroline; Bertran, Françoise; Doidy, Franck; Guénolé, Fabian; Desgranges, Béatrice; Eustache, Francis; RAUCHS, Géraldine (Frontiers in Neurology, 2012)
Sleep plays multiple functions among which energy conservation or recuperative processes. Besides, growing evidence indicate that sleep plays also a major role in memory consolidation, a process by which recently acquired and labile memory traces are progressively strengthened into more permanent and/or enhanced forms. Indeed, memories are not stored as they were initially encoded but rather undergo a gradual reorganization process, which is favoured by the neurochemical environment and the electrophysiological activity observed during sleep. Two putative, probably not exclusive, models (“hippocampo-neocortical dialogue” and “synaptic homeostasis hypothesis”) have been proposed to explain the beneficial effect of sleep on memory processes. It is worth noting that all data gathered until now emerged from studies conducted in young subjects. The investigation of the relationships between sleep and memory in older adults has sparked off little interest until recently. Though, aging is characterized by memory impairment, changes in sleep architecture, as well as brain and neurochemical alterations. All these elements suggest that sleep-dependent memory consolidation may be impaired or occurs differently in older adults. Here, we give an overview of the mechanisms governing sleep-dependent memory consolidation, and the crucial points of this complex process that may dysfunction and result in impaired memory consolidation in aging.